2023
DOI: 10.1021/jacs.3c00860
|View full text |Cite
|
Sign up to set email alerts
|

β-Boron Effect Enables Regioselective and Stereospecific Electrophilic Addition to Alkenes

Abstract: Electrophilic addition to alkenes is a textbook-taught reaction, yet it is not always possible to control the regioselectivity of addition to unsymmetrical 1,2-disubstituted substrates. We report the observation and applications of the β-boron effect that accounts for high regioselectivity in electrophilic addition reactions to allylic MIDA (N-methyliminodiacetic acid) boronates. While the wellestablished β-silicon effect bears partial resemblance to the observed reactivity, the silyl group is typically lost d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Given the propensity for both alkyl and boron groups to migrate, we have investigated the regioselectivity of the reaction, both experimentally and computationally, revealing its dependence on the steric bulk of the diazoacetate substituent. While it has been previously demonstrated that electronic features of the BMIDA group enable regiochemical control, [19] the present study has established how steric effects influence regioselectivity and tautomerization pattern of boryl acetoacetate. If boron migration is desirable in the rearrangement, the benzyl-substituted diazoacetate should be chosen, whereas unsubstituted diazo species give access to b-acylboryl esters.…”
Section: Methodsmentioning
confidence: 58%
“…Given the propensity for both alkyl and boron groups to migrate, we have investigated the regioselectivity of the reaction, both experimentally and computationally, revealing its dependence on the steric bulk of the diazoacetate substituent. While it has been previously demonstrated that electronic features of the BMIDA group enable regiochemical control, [19] the present study has established how steric effects influence regioselectivity and tautomerization pattern of boryl acetoacetate. If boron migration is desirable in the rearrangement, the benzyl-substituted diazoacetate should be chosen, whereas unsubstituted diazo species give access to b-acylboryl esters.…”
Section: Methodsmentioning
confidence: 58%
“…In addition, the formation of a hyperconjugatively stabilized cation G by CÀ B σ-bond was considered as the driving force for the unexpected 1,2hydrogen migration. [24] Both our [20,23] and Szabó/Himo's [21] groups demonstrated the practicality of these protocols through the efficient scale-up synthesis of β-boron substituted gem-difluoroalkanes (Scheme 5a). The synthetic value of the formed products was evidenced by their ability to undergo divergent conversions to other gem-difluorinated molecules by manipulating the CÀ B bond.…”
Section: Synthesis Of β-Boron Substituted Gem-difluoroalkanesmentioning
confidence: 96%
“…Previous joint work from Yudin and us has demonstrated that the sp 3 ‐B hybridized B(MIDA) ( N ‐methyliminodiacetic acid) moiety could exert an intriguing β ‐boron effect, allowing for regioselective and stereospecific electrophilic addition to internal alkenes. [ 11 ] This effect is analogous to the well‐known β ‐silicon effect, [ 12 ] but it shows distinct advantage in that the boryl moiety could be retained in the product. [ 13 ] We thus hypothesized that the same effect might also be applicable to the electrophilic addition reaction of alkynes.…”
Section: Introductionmentioning
confidence: 98%